'Sane' and 'insane' imperialism: British idealism, new liberalism and liberal imperialism. Issue 8 (17th November 2018) - Boucher, David
ABSTRACT: It is contended that British Idealists, New Liberals and Liberal Imperialists were all in favour of imperialism, especially when it took the form of white settler communities. The concession of relative autonomy was an acknowledgement of the potential of white settler communities to go the way of America by severing their relationship with the Empire completely. Where significant differences emerge in their thinking is in relation to non-white territories in the Empire where native peoples comprised the majority, and the British Government and its agents administered in trust 'lower' peoples on the scale of civilisation with the ostensible goal of guiding them towards self-determination in the Empire. The differences in degree of commitment to these ideals were largely expressed in terms of the pejorative categories of 'sane' and 'insane' imperialism, which were flexible and manipulated for political gain, rather than analytic precision. Liberal Imperialists and New Liberals were opposed to each other in terms of the degree to which they supported imperialism, whereas British Idealists aligned themselves on both sides of the divide.